Motivational Factors in Medical Major Selection and Learning Processof Medical Students at Universitas Mulawarman (2024/2025) - Elsadai Pabatta; Dyah Ayu Dian Arini Masithoh; Muhammad Dzaki Habibi; Tomy Adrian Hefotaven Abdulloh; Muhammad Nasywaan Arshia Ramadhan; Emir Muhammad Hajid; Gregory WilterEmmanuel Nathan; Basa Rahelyia Pangaribuan; Amalia Basri; Vidya Hapsari Putri; Khairunnida Rahma (Faculty of Public Health Mulawarman University, Indonesia, 2025)
The decision to pursue a medical major is influenced by multiple factors, such as personal interest, the desire to help others, family expectations, and societal perceptions of the profession’s prestige. These factors play a crucial role in shaping students’ motivation, commitment, and consistency throughout their medical education. This study aims to examine the influence of motivation in choosing a medical major on the learning process of medical students at Universitas Mulawarman. A quantitative research design was employed using a survey method involving 51 medical students from the Faculty of Medicine. Primary data were collected through a structured questionnaire developed based on the Self-Determination Theory (SDT), administered online via Google Forms, and analyzed using linear regression. The analysis revealed a positive relationship between students’ motivation in choosing the medical major and their learning process. Both intrinsic and extrinsic motivations showed a significant influence on students’ engagement and consistency in academic activities, with intrinsic motivation demonstrating a stronger effect. The regression analysis indicated that motivation contributed significantly to variations in students’ learning behavior (p < 0.05). The findings suggest that students who choose the medical major based on intrinsic motivation tend to exhibit higher learning commitment and better adaptation throughout their studies. Therefore, understanding and fostering intrinsic motivation among medical students is essential for improving academic performance and enhancing the overall quality of medical education.